2017
DOI: 10.1021/acsami.6b13074
|View full text |Cite
|
Sign up to set email alerts
|

Strong Strain Sensing Performance of Natural Rubber Nanocomposites

Abstract: A detail study concerning the strain (tensile) dependent electrical conductivity of elastomeric composites is reported in this present paper. Multiwall carbon nanotubes (CNT), conducting carbon black (CB), and their combinations were considered as conducting filler in cross-linked natural rubber matrix. The loadings of the fillers were considered from 3 to 11 phr (filler concentration close to their percolation threshold). Without hindering the elastic nature of the composite (reversible stretchability up to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
116
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 68 publications
(114 reference statements)
3
116
1
Order By: Relevance
“…Furthermore, in Figure 8, the optimal conductivity of the vulcanizates with CNT/CCB hybrid filler was higher than with solely CCB or CNT. This correlates well to the previous work [28] which showed significantly the improvement of the conductivity of the NR composites with CCB/CNT hybrid filler. In addition, in Figure 8, it was found that the conductivity and percolation concentration were again improved by addition of TESPT silane coupling agent.…”
Section: Electrical and Morphological Propertiessupporting
confidence: 92%
“…Furthermore, in Figure 8, the optimal conductivity of the vulcanizates with CNT/CCB hybrid filler was higher than with solely CCB or CNT. This correlates well to the previous work [28] which showed significantly the improvement of the conductivity of the NR composites with CCB/CNT hybrid filler. In addition, in Figure 8, it was found that the conductivity and percolation concentration were again improved by addition of TESPT silane coupling agent.…”
Section: Electrical and Morphological Propertiessupporting
confidence: 92%
“…In recent years, graphene has received a tremendous amount of attention as a kind of unique filler to produce polymer nanocomposites with high performance and novel functionalities for applications such as reinforced nanocomposites, electrically conductive composites, ultrasensitive sensors, and supercapacitor electrodes . Graphene nanofillers have been extensively used in rubber nanocomposites on account of their small size and the corresponding increase in the surface area allowing significant improvement in the matrix properties at low filler loadings . Because conductive fillers have the very poor stretchability, it is imperative to design proper surface structure on elastic substrates and make an effective combination of conductive nanofillers with substrates, which both determine the sensing properties of the resultant sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many attempts have been made to address this conflict and achieve a large stretchability (>100%) and high gauge factor (>20) simultaneously in a single sensor platform . The unique architectures of CNTs, with their aligned wavy bundles and highly oriented fibers, have the potential to enhance the sensing performance by appropriately modulating the contact area between the CNTs upon stretching.…”
Section: Introductionmentioning
confidence: 99%
“…The piezoresistive responses of strain sensors based on elastomeric composites with conductive nanofillers (e.g., CNTs, CBs, mNWs, mNPs, and graphene) are highly dependent on the shape of the nanofillers. It is generally known that composite sensors with particle‐shaped nanofillers exhibit high piezoresistivity in the low strain regime, while wire (1D) and sheet‐shaped (2D) nanofiller‐based composite sensors can function even at relatively high strains with no electrical failure . In a synergistic approach, multidimensional hybrid nanofillers with mixed morphologies, such as CNT/CB and graphene/mNP, were used to form a material with superior piezoresistive behavior over a wide strain range compared to their single‐dimensional counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation